2021
DOI: 10.3390/ijms22094520
|View full text |Cite
|
Sign up to set email alerts
|

The AFLATOX® Project: Approaching the Development of New Generation, Natural-Based Compounds for the Containment of the Mycotoxigenic Phytopathogen Aspergillus flavus and Aflatoxin Contamination

Abstract: The control of the fungal contamination on crops is considered a priority by the sanitary authorities of an increasing number of countries, and this is also due to the fact that the geographic areas interested in mycotoxin outbreaks are widening. Among the different pre- and post-harvest strategies that may be applied to prevent fungal and/or aflatoxin contamination, fungicides still play a prominent role; however, despite of countless efforts, to date the problem of food and feed contamination remains unsolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…On the other side, if antifungal properties of both botanicals and pure compounds isolated from C. colocynthis have been variously described against some phytopathogens (for example, a mixture of spinasterol and 22,23-dihydrospinasterol obtained from the leaves [ 49 ], our observations didn’t provide any significant cue with respect to the aflatoxigenic species selected in this study. However, findings showing the absence of any antifungal or fungistatic potential of extracts on the A. flavus mycelium long-term growth weren’t completely unexpected: in fact, various studies have reported that several compounds, both synthetic and natural, are effective in lowering AF production without apparently interfering with the fungal hyphae elongation or mycelium development [ 13 , 50 , 51 , 52 , 53 ]; this phenomenon has been ascribed to the induction of physiological responses that possibly affect hyphal branching but not apex elongation, and thus result in unaltered colony marginal expansion—which is necessary for efficient colonization and utilization of the substrate. However, the lack of a manifest antifungal effect clearly doesn’t exclude the possibility of an extract’s interaction with other aspects of fungal development.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, if antifungal properties of both botanicals and pure compounds isolated from C. colocynthis have been variously described against some phytopathogens (for example, a mixture of spinasterol and 22,23-dihydrospinasterol obtained from the leaves [ 49 ], our observations didn’t provide any significant cue with respect to the aflatoxigenic species selected in this study. However, findings showing the absence of any antifungal or fungistatic potential of extracts on the A. flavus mycelium long-term growth weren’t completely unexpected: in fact, various studies have reported that several compounds, both synthetic and natural, are effective in lowering AF production without apparently interfering with the fungal hyphae elongation or mycelium development [ 13 , 50 , 51 , 52 , 53 ]; this phenomenon has been ascribed to the induction of physiological responses that possibly affect hyphal branching but not apex elongation, and thus result in unaltered colony marginal expansion—which is necessary for efficient colonization and utilization of the substrate. However, the lack of a manifest antifungal effect clearly doesn’t exclude the possibility of an extract’s interaction with other aspects of fungal development.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their versatility, TSCs display a broad spectrum of biological activities such as being antifungal [ 10 , 11 ], antibacterial [ 12 ], and antiviral [ 13 ]; the biological profiles could be enhanced by complexation with metal ions and the active compounds are normally planar molecules consisting of a pyridine ring in an N,N,S tridentate system [ 6 ]. Furthermore, a number of TSC derivatives were synthesised and reported as potential anticancer agents both in vitro [ 14 ] and in vivo [ 15 ], as free ligands [ 16 ], and as metal complexes [ 17 ], against several cancer types.…”
Section: Introductionmentioning
confidence: 99%